NON-STANDARD PROBLEMS AS A MECHANISM FOR DEVELOPING STUDENTS' CREATIVE THINKING (World Bulletin of Social Sciences, 2023)
This article is dedicated to rais creative capabilite of scool children in teaching mathematics. This txis article gives an account of exsercise training and exsercises in the tepe of searding and methots of problem solving